T lymphocyte characteristics and immune repertoires in the epicardial adipose tissue of heart failure patients - Zhang, Xu-Zhe; Chen, Xian-Li; Tang, Ting-Ting; Zhang, Si; Li, Qin-Lin; Xia, Ni; Nie, Shao-Fang; Zhang, Min; Zhu, Zheng-Feng; Zhou, Zi-Hua; Dong, Nian-Guo; Cheng, Xiang (Frontiers in Immunology, 2023)
Background: Epicardial adipose tissue (EAT) acts as an active immune organ and plays a critical role in the pathogenesis of heart failure (HF). However, the characteristics of immune cells in EAT of HF patients have rarely been elucidated. Methods: To identify key immune cells in EAT, an integrated bioinformatics analysis was performed on public datasets. EAT samples with paired subcutaneous adipose tissue (SAT), heart, and peripheral blood samples from HF patients were collected in validation experiments. T cell receptor (TCR) repertoire was assessed by high-throughput sequencing. The phenotypic characteristics and key effector molecules of T lymphocytes in EAT were assessed by flow cytometry and histological staining. Results: Compared with SAT, EAT was enriched for immune activation-related genes and T lymphocytes. Compared with EAT from the controls, activation of T lymphocytes was more pronounced in EAT from HF patients. T lymphocytes in EAT of HF patients were enriched by highly expanded clonotypes and had greater TCR clonotype sharing with cardiac tissue relative to SAT. Experiments confirmed the abundance of IFN-γ+ effector memory T lymphocytes (TEM) in EAT of HF patients. CCL5 and GZMK were confirmed to be associated with T lymphocytes in EAT of HF patients. Conclusion: EAT of HF patients was characterized by pronounced immune activation of clonally expanded IFN-γ+ TEM and a generally higher degree of TCR clonotypes sharing with paired cardiac tissue.